2021
DOI: 10.1101/2021.09.04.21263115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Durability analysis of the highly effective BNT162b2 vaccine against COVID-19

Abstract: SARS-CoV-2 breakthrough infections have been increasingly reported in fully vaccinated individuals. We conducted a test-negative case-control study to assess the durability of protection after full vaccination with BNT162b2, defined as 14 days after the second dose, against polymerase chain reaction (PCR)-confirmed symptomatic SARS-CoV-2 infection, in a national medical practice between February 1, 2021 and August 22, 2021. We fit conditional logistic regression (CLR) models stratified on residential county an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…9 Further, there have been reports of reduced vaccine effectiveness over time and against emerging variants, resulting in more breakthrough infections, which have spurred discussions regarding strategies to boost and prolong immunity in previously vaccinated individuals. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] With ongoing efforts to distribute initial vaccination series throughout the world and booster doses in the United States and elsewhere, it is important to understand whether one mRNA vaccine confers stronger protection than the other. Here, we begin to address this knowledge gap by retrospectively comparing the rates of symptomatic SARS-CoV-2 infection after full vaccination with mRNA-1273 versus BNT162b2 in the multi-state Mayo Clinic Health System.…”
Section: Context and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…9 Further, there have been reports of reduced vaccine effectiveness over time and against emerging variants, resulting in more breakthrough infections, which have spurred discussions regarding strategies to boost and prolong immunity in previously vaccinated individuals. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] With ongoing efforts to distribute initial vaccination series throughout the world and booster doses in the United States and elsewhere, it is important to understand whether one mRNA vaccine confers stronger protection than the other. Here, we begin to address this knowledge gap by retrospectively comparing the rates of symptomatic SARS-CoV-2 infection after full vaccination with mRNA-1273 versus BNT162b2 in the multi-state Mayo Clinic Health System.…”
Section: Context and Significancementioning
confidence: 99%
“…Indeed, we and others have recently found that protection against SARS-CoV-2 infection wanes over time after full vaccination with BNT162b2, and a similar trend has been suggested for mRNA-1273. 16,17,[19][20][21]28,29 Several factors could contribute to the observed differences in effectiveness of mRNA-1273 and BNT162b2. Although both are nucleoside-modified mRNA vaccines encoding the prefusion stabilized SARS-CoV-2 Spike protein, there are differences in the vaccination regimen and formulation.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Third, since mid-August, the VP constantly decreased from around 84% in August to around 60% in November. This probably signals waning immunity [ 9 , 12 , 13 ]. Time since vaccination is systematically longer for older age groups ( Figure 2 ), potentially increasing the effect of waning immunity visible in our data.…”
Section: Calculation Of 14-day Notification Rates and Relative Risks ...mentioning
confidence: 99%
“…Our model includes the effect of vaccination, where vaccines are for simplicity administered with a singledosage delivery scheme. Vaccinated individuals cannot be infected while being in the vaccinated compartment, but will proceed to the waned immunity compartment W v at a rate Ω [52,53]. The same applies to recovered individuals, who also lose their post-infection immunity at rate Ω [54].…”
Section: S14 Vaccination Effects and Waning Immunitymentioning
confidence: 99%